2022
DOI: 10.1039/d1nr06001e
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogel-mediated topical delivery of steroids can effectively alleviate psoriasis via attenuating the autoimmune responses

Abstract: Psoriasis is a systemic, relapsing, and chronic autoimmune inflammatory disease of the skin. Topical use of betamethasone, a glucocorticoid, in the form of creams is commonly used for treatment of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Hydrogels, owing to their biochemical characteristics of good retention, avoidance of drug leakage, good hydrophilicity and adhesiveness, have been identified as the most competitive candidate for the percutaneous treatment of inflammatory diseases [ 164 166 ]. Considerable research has demonstrated that hydrogels can be well-appointed with tunable functions via the incorporation of various bioactive substances, such as nanoparticles and drugs and establish well-pleasing biomedical applications in transdermal drug delivery [ 190 , 217 220 ]. As shown in Fig.…”
Section: Latest Developments Of Biomaterials For Psoriasis Therapiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Hydrogels, owing to their biochemical characteristics of good retention, avoidance of drug leakage, good hydrophilicity and adhesiveness, have been identified as the most competitive candidate for the percutaneous treatment of inflammatory diseases [ 164 166 ]. Considerable research has demonstrated that hydrogels can be well-appointed with tunable functions via the incorporation of various bioactive substances, such as nanoparticles and drugs and establish well-pleasing biomedical applications in transdermal drug delivery [ 190 , 217 220 ]. As shown in Fig.…”
Section: Latest Developments Of Biomaterials For Psoriasis Therapiesmentioning
confidence: 99%
“…12 b) [ 221 ]. Additionally, Kajal Rana et al presented that a betamethasone-loaded topical hydrogel (B-Gel) which can efficiently entrap steroids with the properties of spreadability and sustained release drugs, provided an alternative for topical application of steroids [ 220 ]. Moreover, implementing biocompatible hydrogel micropatch probes integrated with mass spectrometry to explore the skin metabolome could be regarded as a diagnostic approach to provide information about the pathological alterations of the skin metabolome caused by psoriasis, favoring understanding of the complicated pathophysiology.…”
Section: Latest Developments Of Biomaterials For Psoriasis Therapiesmentioning
confidence: 99%
“…In psoriasis management, hydrogels usually work for sustained anti-psoriatic drug release. 38,[121][122][123][124][125] For instance, early in 1992, Ormerod et al prepared a dithranolimpregnated hydrogel to treat psoriasis. The drug-loaded hydrogel was fabricated by directly adding dithranol solution to the preformed polyurethaneurea hydrogel film for drying.…”
Section: Hydrogelsmentioning
confidence: 99%
“…In a recent study, Rana et al developed a betamethasone-loaded topical hydrogel (B-Gel) for psoriasis treatment. 125 The hydrogel was prepared by heating and cooling the mixture solution of betamethasone and A6 gelator. The hydrogel could efficaciously overcome the drawbacks of the ineffective entrapment of steroids, burst release of the entrapped drugs, poor skin permeability, and high toxicity, which finally mitigate psoriasis associated symptoms.…”
Section: Hydrogelsmentioning
confidence: 99%
“…By detecting the expression levels of various proteins through Western blot (Figure5e−k), it can be seen that compared with IMQ, Cur-Car-IL@Ilo hydrogel, the expression of SLC7A11 and ASL4 in the group was significantly reduced, while there was no difference in the expression of MMP-8, collagen-I, GPX4, and FSP1. After local medication treatment, the Cur-Car-IL@Ilo hydrogel can reduce the expression of SLC7A11 and ASL4 36,45,46. 3.6.…”
mentioning
confidence: 99%